2020
DOI: 10.1080/08039488.2020.1841289
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspectives on three-monthly administration of antipsychotic treatment with paliperidone palmitate – a qualitative interview study

Abstract: Introduction: Three-monthly dosage of paliperidone palmitate entails longer time to relapse after discontinuation, is similarly tolerable and safe compared to monthly injections of paliperidone palmitate and is beneficial for the caregivers. However, few studies have so far explored in depth the patients' experiences with paliperidone palmitate medication every three months, or with switching from monthly to three-monthly injections of paliperidone palmitate. Material and methods: A qualitative study based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Previous studies found either that the transition from PP1M to PP3M was associated with a decline in outpatient and pharmacy visits 24 or that contact frequency was not influenced by PP3M. 18 Our results suggest that this may be individually determined, essentially supporting both findings, with approximately half of our participants reporting an unchanged number of contact moments (53%) and the other half reporting a reduced number of contact moments (42%). Although our participants did not specify the reasons for any of their visits, it is likely that at least the visits exclusively intended for PP3M injections (four times a year) were less frequent compared to PP1M (twelve times a year).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies found either that the transition from PP1M to PP3M was associated with a decline in outpatient and pharmacy visits 24 or that contact frequency was not influenced by PP3M. 18 Our results suggest that this may be individually determined, essentially supporting both findings, with approximately half of our participants reporting an unchanged number of contact moments (53%) and the other half reporting a reduced number of contact moments (42%). Although our participants did not specify the reasons for any of their visits, it is likely that at least the visits exclusively intended for PP3M injections (four times a year) were less frequent compared to PP1M (twelve times a year).…”
Section: Discussionsupporting
confidence: 84%
“… 17 From a patient’s perspective, individual depth-interviews with 24 patients with schizophrenia revealed that they had more feelings of stability and were more physically and socially active after they received PP3M. 18 The authors concluded that switching from PP1M to PP3M seemed to be experienced as advantageous for patients with psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%